2018
DOI: 10.3390/bs8020026
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of neuroEPO Using an In Vitro Model of Stroke

Abstract: Erythropoietin (EPO) is a glycoprotein initially identified as a hormone synthesized and secreted by the kidney that regulates erythropoiesis. EPO, and a group of its derivatives, are being evaluated as possible neuroprotective agents in cerebral ischemia. The objective of this study, using an in vitro model, was to determine how neuroEPO—which is a variant of EPO with a low sialic acid content—protects neurons from the toxic action of glutamate. Primary neuronal cultures were obtained from the forebrains of W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Overexpressed EPO improved rat heart fibrosis through the PI3K/Akt/TLR4 pathway to suppress the release of mediators such as TGF-β1, proinflammatory cytokines, and matrix metalloproteinase [58]. EPO exerts neuroprotective effect in neurodegenerative diseases [104], ischemic brain injury [105,106], spinal cord injury [107] and motor neuron death post-burn [69]. EPO has also been found to improve muscular dysfunction in various experimental models, possible through increasing autophagy as well as decreasing apoptosis in type 2 diabetic skeletal muscles [65], reducing apoptosis in a crushing injury model [108] and preventing cancer-induced muscle alteration [67].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpressed EPO improved rat heart fibrosis through the PI3K/Akt/TLR4 pathway to suppress the release of mediators such as TGF-β1, proinflammatory cytokines, and matrix metalloproteinase [58]. EPO exerts neuroprotective effect in neurodegenerative diseases [104], ischemic brain injury [105,106], spinal cord injury [107] and motor neuron death post-burn [69]. EPO has also been found to improve muscular dysfunction in various experimental models, possible through increasing autophagy as well as decreasing apoptosis in type 2 diabetic skeletal muscles [65], reducing apoptosis in a crushing injury model [108] and preventing cancer-induced muscle alteration [67].…”
Section: Discussionmentioning
confidence: 99%
“…Besides antioxidants, the research of molecules that act on mitochondria represents an innovative approach aimed at mitigating local ROS production or at reducing their induced damage (Brieger et al, 2012). These compounds include EPO, a cytokine induced by hypoxia expressed in the brain that has been demonstrated to exert many fundamental effects such as neuroprotection and neuroregeneration (Brines and Cerami, 2005;Carelli et al, 2018;Digicaylioglu et al, 1995;Rey et al, 2021bRey et al, , 2019, neurodevelopment (Victor et al, 2021), neuroplasticity (Brines and Cerami, 2005), when stimulated by mild local hypoxia (Wakhloo et al, 2020) or when administered as recombinant human (rh)EPO in different in vitro and in vivo pre-clinical experimental models (Fernando et al, 2018;Maurice et al, 2013;Rey et al, 2021bRey et al, , 2019. The neuroprotective effects of rhEPO have been demonstrated also in two clinical trials in PD affected patients (Jang et al, 2014;Pedroso et al, 2012).…”
Section: Targeting Of O 2 Imbalance: Consequences For the Amelioratio...mentioning
confidence: 99%
“…The study concluded that neuro-EPO application starting within 12 h after ischemia improved neurological scores and behavior of the spontaneous exploratory activity after 7 days of ischemia ( Teste et al, 2012 ). Using an in vitro model of cerebral ischemia, in which oxidative stress was induced by glutamate in cultured neurons, neuro-EPO (100 ng/ml) treatment preserved neurons from oxidative stress through upregulation of Bcl-2 and inhibition of glutamate-induced caspase-3 activation ( Fernando et al, 2018 ; Garzón et al, 2018 ). In addition, neuro-EPO was used in AD models and showed improvement in cognitive function ( Maurice et al, 2013 ; Rodríguez Cruz et al, 2017 ).…”
Section: Epo Derivative Treatment For Ischemic Strokementioning
confidence: 99%